Study Evaluation of the Impact of Teacher Pedagogic Competency on Early Childhood Discipline in Bekasi Kindergarten - Ajat, Ajat; Kurniati, Nia (Kirana Publisher (KNPub), 2025)
This study aims to identify the evaluation of the impact of teachers' pedagogical competence on the discipline of early childhood students at TK Islam Al Fajar Jatiasih, Bekasi City. This research employs a qualitative approach. Data collection was conducted through interviews with teachers, school supervisors, and parents of the students. The research design uses the CIPP evaluation model. The study shows that the pedagogical competence of teachers at TK Islam Al Fajar significantly influences the development of early childhood discipline through a constructivist approach that involves planned activities and active student participation, thereby creating a learning environment that supports understanding of discipline and responsibility. The tangible impact of teachers' pedagogical competence is seen in the positive changes in students' obedient and disciplined attitudes, and the collaboration between teachers and parents strengthens the enforcement of rules, creating consistency that supports character development.